Transformasi Digital UMKM Melalui Pendampingan QRIS dan Google Business Profile di Desa Padang Peri - Putri Nabila; Merli Merli; Anisah Friti Anjelia; Agustina Dwi Putri Situmeang; Afidatu Tsaniyah; Nadilah Dhiya Karimah; Ade Yudistira; Aldian Satria Kesuma; Kevin Dwi Prasetya; M.Gading Laksono; Saprinurdin (Jurnal Ekonomi dan Bisnis Digital, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting local economic growth and community welfare. However, many rural MSMEs still face challenges in adopting digital technology for business development. This study aims to analyze the digital transformation of MSMEs through assistance in creating Google Business Profiles and providing education on the Quick Response Code Indonesian Standard (QRIS) in Padang Peri Village. A descriptive qualitative approach was employed using observation, interviews, documentation, and direct mentoring as the primary data collection methods. The study involved eleven MSMEs operating in various business sectors within the village. The findings reveal that all participating MSMEs successfully established Google Business Profiles according to their respective business categories, improving their online visibility and enabling customers to access business information more easily through Google Search and Google Maps. Nevertheless, the adoption of QRIS remained relatively low because many business owners had limited knowledge regarding its benefits, security, and operational procedures, and continued to rely on cash transactions. Despite these challenges, the mentoring program received positive responses from MSME owners and the village government, reflecting strong community support for digital transformation initiatives.Continuous assistance, digital literacy enhancement, and collaboration among stakeholders are essential to accelerate QRIS adoption, strengthen digital marketing capabilities, improve business competitiveness, and support the sustainable development of MSMEs in the digital economy.